Вычислить:
$$19. [\frac{(6 - 4\frac{1}{2}) : 0,03}{(3\frac{1}{20} - 2,65) \cdot 4 + \frac{2}{5}} - \frac{(0,3 - \frac{3}{20}) \cdot 1\frac{1}{2}}{(1,88 + 2\frac{3}{25}) \cdot \frac{1}{80}}] : 2\frac{1}{20}.$$
Решение:
\(19. [\frac{(6 - 4\frac{1}{2}) : 0,03}{(3\frac{1}{20} - 2,65) \cdot 4 + \frac{2}{5}} - \frac{(0,3 - \frac{3}{20}) \cdot 1\frac{1}{2}}{(1,88 + 2\frac{3}{25}) \cdot \frac{1}{80}}] : 2\frac{1}{20} = 10.\)

\(
1) 6 - 4\frac{1}{2} = 6 - 4,5 = 1,5;
\)

\(
2) 1,5 : 0,03 = 50;
\)

\(
3) 3\frac{1}{20} - 2,65 = 3\frac{5}{100} - 2,65 = 3,05 - 2,65 = 0,4.
\)

\(
4) 0,4 \cdot 4 = 1,6;
\)

\(
5) 1,6 + \frac{2}{5} = 1,6 + \frac{4}{10} = 1,6 + 0,4 = 2;
\)

\(
6) 50 : 2 = 25;
\)

\(
7) 0,3 - \frac{3}{20} = 0,3 - \frac{15}{100} = 0,3 - 0,15 = 0,15;
\)

\(
8) 0,15 \cdot 1\frac{1}{2} = \frac{15}{100} \cdot \frac{3}{2} = \frac{3}{20} \cdot \frac{3}{2} = \frac{9}{40};
\)

\(
9) 1,88 + 2\frac{3}{25} = 1,88 + 2\frac{12}{100} = 1,88 + 2,12 = 4;
\)

\(
10) 4 \cdot \frac{1}{80} = 1 \cdot \frac{1}{20} = \frac{1}{20};
\)

\(
11) \frac{9}{40} : \frac{1}{20} = \frac{9}{40} \cdot \frac{20}{1} = \frac{9 \cdot 20}{40 \cdot 1} = \frac{9 \cdot 1}{2 \cdot 1} = \frac{9}{2} = 4\frac{1}{2};
\)

\(
12) 25 - 4,5 = 20,5;
\)

\(
13) 20,5 : 2\frac{1}{20} = 20,5 : 2\frac{5}{100} = 20,5 : 2,05 = 10.
\)
Ответ: 10.

Добавить комментарий


Защитный код
Обновить